Algal Flora of Barju (Chimdi) Taal, Sunsari District, Province 1, Nepal - Rai, Shiva Kumar; Chaudhary, Laxmi; Ghimire, Narayan Prasad; Dhakal, Sajita (Journal of Plant Resources, 2022)
The algal flora of Barju Taal (Lake) has been studied in 2017-18 AD. The lake is situated in Barju Rural Municipality, Sunsari District, Eastern Nepal about 12 km west of Biratnagar covering an area of 101.6 hectares. Algae were collected by squeezing submerged aquatic plants. A total of 105 algae under 51 genera have been reported. The largest phylum was chlorophyta (76 species) followed by bacillariophyta (16 species), cyanobacteria (11 species) and euglenozoa (2 species). Similarly, the largest genus was Cosmarium (22.85%) followed by Staurastrum (8.57%) and Euastrum (4.76%). Algae common to Barju Taal were Dictyosphaerium pulchellum, Ankistrodesmus falcatus, Closterium dianae, Euastrum elegans, Actinotaenium subglobosum, Cosmarium quadrum, C. ralfsii, Staurodesmus unicornis, Staurastrum sonthalianu and S. striolatum. Old Barju Taal was rich in algae than the newly constructed one. Further study of algae in different seasons compared with water parameters is recommended